A homozygous CAP2 pathogenic variant in a neonate presenting with rapidly progressive cardiomyopathy and nemaline rods. Issue 3 (4th December 2021) - Gurunathan, Sharavana; Sebastian, Jessica; Baker, Jennifer; Abdel‐Hamid, Hoda Z.; West, Shawn C.; Feingold, Brian; Peche, Vivek; Reyes‐Múgica, Miguel; Madan‐Khetarpal, Suneeta; Field, Jeffrey
Abstract: Nemaline Myopathy (NM) is a disorder of skeletal muscles caused by mutations in sarcomere proteins and characterized by accumulation of microscopic rod or thread‐like structures (nemaline bodies) in skeletal muscles. Patients diagnosed with both NM and infantile cardiomyopathy are very rare. A male infant presented, within the first few hours of life, with severe dilated cardiomyopathy, biventricular dysfunction and left ventricular noncompaction. A muscle biopsy on the 8th day of life from the right sternocleidomastoid muscle identified nemaline rods. Whole exome sequencing identified a c.1288 delT (homozygous pathogenic variant) in the CAP2 gene (NM_006366), yielding a CAP2 protein (NP_006357.1) with a p.C430fs. Both parents were heterozygous for the same variant but have no history of heart or muscle disease. Analysis of patient derived fibroblasts and cardiomyocytes derived from induced pluripotent stem cells confirmed the p.C430fs mutation (pathogenic variant), which appears to cause loss of both CAP2 protein and mRNA. The CAP2 gene encodes cyclase associated protein 2, an actin monomer binding and filament depolymerizing protein and CAP2 knockout mice develop severe dilated cardiomyopathy and muscle weakness. The patient underwent a heart transplant at 1 year of age. Heart tissue explanted at that time also showed nemaline rods and additionally disintegration of the myofibrillar structure. Other extra cardiac concerns include mild hypotonia, atrophic and widened scarring. This is the first description of a patient presenting with nemaline myopathy associated with a pathogenic variant of CAP2.